Seeing by Electricity : The Emergence of Television, 1878-1939 - Galili, Doron (Book collections on Project MUSE., 2020)
"SEEING BY ELECTRICITY traces an early history of television--from 19th-century imaginaries of a technology that would allow viewers to see by electricity to an institutionalized medium subject to government regulation and telecommunications corporations. Throughout, Doron Galili demonstrates that the early histories of television and cinema were more intertwined than scholars and industry historians have ever acknowledged. In the 1870s, animated photographs and the electrical transmission of images were conceived of as two distinct formations of moving image media. Standard media histories have thus understood the initial development of television and cinema technologies as two separate, but parallel, processes that each took place between the 1870s and World War I. Yet in this new history of early television, Galili shows that television was always discussed in relation to cinema. In the first few chapters, Galili shows that while the earliest discourses on devices for transmitting moving images considered this to be an extension of telegraph and telephone technologies, early cinema developed out of a very different media environment of scientific imaging techniques, magic and vaudeville shows, and lantern projections. Cultural narratives about moving image transmission technologies assumed that an inevitable technological progress would lead from the telegram to sound and image transmission technologies. The electricians, physicists, telegraph technicians, and engineers who developed technological schemes for television imagined an apparatus that would "see" by electricity, a prosthetic vision device that would complement or substitute for human perception. Yet, by taking a media archaeological approach, Galili demonstrates that scientists, cultural critics, and theorists of the time didn't recognize a clear dichotomy between recording and transmission. Galili considers the experimental era of television network broadcasting in the US and looks at film depictions of television like Murder By Television and S.O.S. Tidal Wave, which themselves explored the distinctions between transmitted and cinematographic visual media. The final chapters of the book consider early ideas about television in the Soviet Union, Germany, and Italy. While early-20th-century Hollywood saw the prospect of the non-photographic moving image as a potential threat, modernist avant-garde projects in Europe considered TV an exciting alternative to film. SEEING BY ELECTRICITY will interest students and scholars of film and TV studies, history of technology, media studies, and American cultural history"--